Nel giardino di Pomona: le "Metamorfosi" di Ovidio e l'invenzione di una mitologia in terra d'Italia - Aresi, Laura (Bibliothek der klassischen Altertumswissenschaften / 2, 2017)
Books 14-15 of the "Metamorphoses" present the problematic landing of the narration of the poem in the "Latium vetus", a frame of stories that return to the mythical Greek past. The present volume aims to reflect on this difficult interaction between "Greek" and "Romanity" in a somewhat different perspective compared to that which has been consolidated in the most recent Ovidian studies: how is the Greek myth presented? And who says it? How does the setting affect the fate of the characters in the setting? From the perspective of the "last three myths" of the poem's love affair, the book traces a path that leads to a gradual reversal of the relations of force between "content" and "container" of the story: if the Greek myth fades away, made immortal by a reputation that condemns him to immutability, a newborn Italian myth takes shape in the gardens of a Lazio that becomes the right place to stage stories without a past and without a 'future' already written. The poet who, for excellence, has forced all the limits of the story in the variation of the already known is found to cross the boundaries of that same tradition in which everyone has always seen it so at ease
Dissertation unter dem Titel: Da Circe ad Egeria: le nuove vie del mito in terra d'Italia (Ov. Met. 14-15) --- Titelblattrückseite
Überarbeitete und bibliographisch aktualisierte Fassung der Dissertation
Literaturverzeichnis: Seiten 321-339
Keywords: Ovid -- 43 B.C.-17 A.D. or 18 A.D -- Metamorphoses -- Liber 14-15; Hochschulschrift; Mythologie; Latium; Ovidius Naso, Publius / Metamorphoses 15; Ovidius Naso, Publius / Metamorphoses 14; Italien; Rezeption; Griechenland; Ovidius Naso, Publius / Metamorphoses